Sigma-1 Receptor: A Potential Therapeutic Target for Traumatic Brain Injury - Shi, Mingming; Chen, Fanglian; Chen, Zhijuan; Yang, Weidong; Yue, Shuyuan; Zhang, Jianning; Chen, Xin (Frontiers in Cellular Neuroscience, 2021)
The sigma-1 receptor (Sig-1R) is a chaperone receptor that primarily resides at the mitochondria-associated endoplasmic reticulum (ER) membrane (MAM) and acts as a dynamic pluripotent modulator regulating cellular pathophysiological processes. Multiple pharmacological studies have confirmed the beneficial effects of Sig-1R activation on cellular calcium homeostasis, excitotoxicity modulation, reactive oxygen species (ROS) clearance, and the structural and functional stability of the ER, mitochondria, and MAM. The Sig-1R is expressed broadly in cells of the central nervous system (CNS) and has been reported to be involved in various neurological disorders. Traumatic brain injury (TBI)-induced secondary injury involves complex and interrelated pathophysiological processes such as cellular apoptosis, glutamate excitotoxicity, inflammatory responses, endoplasmic reticulum stress, oxidative stress, and mitochondrial dysfunction. Thus, given the pluripotent modulation of the Sig-1R in diverse neurological disorders, we hypothesized that the Sig-1R may affect a series of pathophysiology after TBI. This review summarizes the current knowledge of the Sig-1R, its mechanistic role in various pathophysiological processes of multiple CNS diseases, and its potential therapeutic role in TBI.